2005
DOI: 10.1128/jb.187.3.1192-1195.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phospholipase Activity of the Pseudomonas aeruginosa Type III Cytotoxin, ExoU

Abstract: Recombinant ExoU (rExoU) and yeast extract were used to optimize an in vitro phospholipase assay as a basis for identifying the mechanism for enzyme activation and substrate specificity. Our results support a model in which a eukaryotic protein cofactor or complex facilitates the interaction of rExoU with phospholipid substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 21 publications
2
80
0
Order By: Relevance
“…1B) and substantially diminished activation of ExoU (Fig. 1C), indicating that ubiquitin was necessary for membrane fraction activation of ExoU (14). We next tested whether protease-treated membrane fraction could activate ExoU in the presence of small amounts of exogenous ubiquitin (i.e., concentrations of ubiquitin below those needed for detectable activation).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B) and substantially diminished activation of ExoU (Fig. 1C), indicating that ubiquitin was necessary for membrane fraction activation of ExoU (14). We next tested whether protease-treated membrane fraction could activate ExoU in the presence of small amounts of exogenous ubiquitin (i.e., concentrations of ubiquitin below those needed for detectable activation).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the potent in vitro activation of ExoU by PI(4,5)P2 in combination with ubiquitin, we investigated the biological relevance of this effect in eukaryotic cells. The budding yeast Saccharomyces cerevisiae is a useful model for studying ExoU, as ExoU kills yeast similarly to mammalian cells (14,22). Additionally, both ubiquitin and PI (4,5)P2 are found in all eukaryotes, including yeast (21,31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ExoU exhibits a patatin-like phospholipase activity (Sato et al, 2003;Sato and Frank 2004;Sato et al, 2005) in combination with host factors, e.g. superoxide dismutase (Sato et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Upon activation, the type III secretion apparatus translocates effector molecules into the cytoplasm of host cells, resulting in cell rounding and lifting and cell death by necrosis or apoptosis (Finck-Barbancon et al, 1997;Pederson et al, 1999;Kaufman et al, 2000). There are four known effector molecules, including ExoS and ExoT, two homologous toxins with both ADP-ribosyltransferase and GTPaseactivating protein activities, an acute cytotoxin, ExoU, with lipase activity, and an adenylate cyclase, ExoY (Yahr et al, 1996(Yahr et al, , 1998Finck-Barbancon et al, 1997;Hauser et al, 1998;Sato et al, 2005). It is well known that ExoS preferentially ADP-ribosylates several Ras family members (GTP-binding proteins) required for the regulation of intracellular vesicle transport, cell proliferation and differentiation (Coburn & Gill, 1991;Ganesan et al, 1998).…”
mentioning
confidence: 99%